Disain Alat Utama Menara Distilasi De-Ethanizer Pada Prarancangan Pabrik Benzene, Toluene, Dan Xylene (BTX) Menggunakan Proses Cyclar BP/UOP - Muh. Fadlan Alfuadi; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Benzene, toluene and xylene (BTX) are petrochemical products made from naphtha through a catalytic formation process. Benzene and toluene are some of the products that are widely used in chemical raw materials. One of them is toluene, Toluene is used as a solvent and intermediate in the manufacture of chemicals, high octane components and gasoline, while the need for pxylene is increasing. With the increasing demand for polyester fibers and films. The designed factory production capacity is 602,606 tons per year. One of the main separation tools in this plant is the De-ethanizer. This distillation is designed to separate hydrogen gas, methane, and ethane from the naphtha mixture. De-Ethanizer has operating conditions with a feed temperature of 289 Kelvin, a distillate temperature of 216 Kelvin and a bottom temperature of 306 Kelvin and a pressure of 7,01 bar. The de-etanizer feed flow rate is 147229,0473 lb/hour with the gas phase in the form of a mixture of hydrogen, methane, ethane, and naphtha. The distillate flow rate is 10763,0445 lb/hour with the gas phase in the form of a mixture of hydrogen, methane, and ethane and the bottom flow rate is 136491,2049 lb/hour with the liquid phase in the form of naphtha. The shell material used is SA-285 grade C stainless steel. De-Ethanizer distillation is designed with a height of 9,64 meters, a shell thickness of 1 in and has 20 plates with a sieve tray type. Keyboard: BTX, De-Ethanizer, catalityc reforming, sieve tray